Stability and ductility of structures - Kvedaras, Audronis Kazimieras (Journal of Civil Engineering and Management, 2010)
Stability and ductility of structures The Journal of Civil Engineering and Management, 16(2), p. 155-158. First Published Online: 24 Jun 2011